A composite current collector and its preparation method and application
By using a composite collector with a porous metal intermediate layer and a porous polymer layer structure in a lithium-ion battery, the problem of the mass of the current collector accounting for the total weight and not contributing to capacity is solved, and the energy density of the battery is increased and the thermal runaway is reduced.
Patent Information
- Application Number
- CN202411765711.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-04
AI Technical Summary
In existing lithium-ion batteries, the mass of the current collector accounts for more than 15% of the total weight, but it does not contribute to the capacity, which hinders the improvement of battery energy density, and also has thermal runaway and welding problems.
Using a composite liquid collector structure of a porous metal intermediate layer and a porous polymer layer, the porous polymer layer is located on both sides of the porous metal intermediate layer and fills its holes with metal particles to form a conductive network, reducing the weight of the current collector and improving conductivity.
It significantly improves the mass energy density of the battery cell, improves welding problems, reduces the probability of thermal runaway, and promotes uniform deposition of Li+.
Smart Images

Figure CN119230844B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and relates to a composite current collector and a preparation method and application thereof, and in particular to a composite current collector for lithium-ion batteries and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) have become the dominant technology for portable electronic devices, portable device power supplies, and energy storage due to their long service life and high energy efficiency. Over the past decade, the rapid development of various fields has put forward higher requirements for LIBs, especially higher energy density and better safety. In the traditional LIB structure, copper foil (ρ=8.96g / cm 3 Pure metal current collectors such as aluminum foil or aluminum foil are usually used to support the active materials of the negative and positive electrodes, respectively. However, their combined mass accounts for more than 15% of the total weight of LIBs, but they do not contribute to the capacity, which greatly hinders the improvement of the overall energy density of LIBs.
[0003] In order to meet the high energy density, all battery components (including electrochemically inactive components) in lithium-ion batteries have reached their limits. For example, in the current collector, the thickness of the copper foil is reduced from 20 μm and the thickness of the aluminum foil is reduced from 18 μm to 6-10 μm and 10-15 μm. For example, CN215869466U discloses an ultra-thin and flexible battery current collector, including a substrate layer, a first metal layer located on the upper surface of the substrate layer, and a second metal layer located on the lower surface of the substrate layer; a channel penetrating the substrate layer is provided on the substrate layer, and a conductive layer for electrically connecting and conducting the first metal layer and the second metal layer is provided inside the channel. By providing two mutually conductive metal layers on the substrate layer, the thickness of the battery current collector can be reduced to less than 6 μm, and it is not easy to break. When used, due to the thin thickness, the weight is reduced, and the problem that the weight cannot be reduced under many requirements is also solved. Due to the thin thickness, the space for coating, that is, the increase of the plating layer, is increased under specific conditions. When the metal layer of the battery current collector is above 6μm, due to the presence of the substrate layer sandwiched between the two metal layers, the tensile force is better, the safety performance is higher, and the problems of needle puncture and short circuit are avoided. The battery current collector in the technical case of the above document also has advantages in anti-extrusion and overcharging compared to the existing copper foil layer structure. The technical solution provided by the above document reduces the material cost and increases the energy density of the battery, but further reducing the thickness of the current collector is technically challenging (especially to achieve excellent surface finish and uniformity in packaging production), and complicates the processing of battery assembly and operation. Therefore, how to further reduce the mass of the current collector has become the focus of optimizing the battery structure in the future.
[0004] In addition, with the widespread application of lithium-ion batteries in different fields, the potential safety hazards they present have gradually become the focus of discussion. For example, the precipitation of lithium dendrites at the negative electrode, the shrinkage or melting of the diaphragm, etc., can easily cause the battery to short-circuit and generate a lot of heat. Generally speaking, when the internal temperature of the battery is around 90°C, the SEI film on the electrode surface begins to decompose, and the triggering conditions for battery thermal runaway begin to be established. With the occurrence of a series of chain exothermic reactions, the heating rate inside the battery increases exponentially, and the temperature will quickly approach the ignition point of the flammable electrolyte, causing the battery to burn and explode. Therefore, preventing thermal runaway of lithium-ion batteries and establishing a battery safety prevention and control system are important prerequisites for further upgrading and optimizing lithium-ion batteries in the future.
[0005] Therefore, it is urgently needed to design a technical solution to solve the problems of battery energy density and safety, thereby improving battery performance. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention aims to provide a composite current collector and a preparation method and application thereof. The composite current collector provided by the present invention has improved conductivity and promoted Li + The uniform deposition of lithium ions avoids the existence of lithium dendrites and has a lighter design, which improves the energy density of the battery. It also prevents the rise of heat during thermal runaway of the battery cell and blocks heat diffusion, thereby improving the safety of the battery. In addition, it also improves welding problems and has the advantage of convenience in practical applications.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a composite current collector, the composite current collector comprising:
[0009] A porous metal intermediate layer;
[0010] A porous polymer layer, wherein the porous polymer layer is respectively located on two side surfaces of the porous metal intermediate layer;
[0011] The pores of the porous polymer layer are filled with metal particles.
[0012] It should be noted that the hole structures in the porous metal intermediate layer and the porous polymer layer in the present invention are arranged along the thickness direction of the film layer.
[0013] The composite current collector provided by the present invention adopts a structure in which a metal layer is provided in the middle of two polymer layers, which greatly reduces the weight of the current collector, can significantly improve the mass energy density of the battery core, and has excellent mechanical flexibility, is not prone to breakage, can better avoid the short circuit of the battery, and reduce the probability of thermal runaway; the polymer layer and the metal layer are both porous structures, and the metal particles filled in the porous polymer layer are in contact with the porous metal middle layer, so that the conductive network on the front and back sides of the composite current collector is connected, and no additional electrode ear welding is required, which has the advantage of convenience in practical application, and also improves the problem of poor conductivity caused by the presence of the polymer layer; and promotes Li + The uniform deposition of lithium ions can be achieved, avoiding the existence of lithium dendrites.
[0014] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0015] Preferably, the metal material of the porous metal intermediate layer includes any one of copper, gold or silver, or a combination of at least two of them.
[0016] Preferably, the weight average molecular weight of the polymer in the porous polymer layer is 10,000-30,000.
[0017] Preferably, the polymer in the porous polymer layer includes any one of polyimide, polyvinylidene fluoride, polypropylene, polyethylene, polyethylene terephthalate, polymethyl methacrylate, polyethylene oxide or polyvinyl alcohol, or a combination of at least two thereof.
[0018] Preferably, the pore size in the porous polymer layer is 5-20 μm.
[0019] Preferably, taking the thickness direction perpendicular to the porous polymer layer as the horizontal direction, the hole center distance between holes in adjacent porous polymer layers in the same horizontal direction is 500-5000 μm.
[0020] Preferably, the thickness T1 of the porous polymer layer and the thickness T2 of the porous metal layer satisfy: 2 μm≤T1+T2≤12 μm.
[0021] Preferably, the thickness T1 of the porous polymer layer and the thickness T2 of the porous metal layer satisfy: 1 / 2≤T1 / (T1+T2)≤10 / 12.
[0022] Preferably, the porous polymer layer and the porous metal layer are connected via the metal particles in the holes of the porous polymer layer.
[0023] Preferably, the surface of the porous polymer layer away from the porous metal layer is modified with a first lithiophilic polymer; the first lithiophilic polymer includes any one of polydopamine, polyethylene oxide, polyvinyl alcohol or polyacrylamide, or a combination of at least two thereof.
[0024] Preferably, the surface of the porous polymer layer away from the porous metal layer is also modified with a second lithiophilic polymer, and the second lithiophilic polymer is grafted to the first lithiophilic polymer; the second lithiophilic polymer includes any one of polydopamine, polyethylene oxide, polyvinyl alcohol or polyacrylamide, or a combination of at least two of them.
[0025] In a second aspect, the present invention provides a method for preparing the composite current collector as described in the first aspect, the preparation method comprising the following steps:
[0026] A porous polymer layer is composited on both sides of the porous metal intermediate layer, and then metal particles are filled in the holes of the porous polymer layer to obtain the composite current collector.
[0027] Preferably, the method of composite porous polymer layers on both sides of the porous metal intermediate layer comprises: providing non-porous polymer layers on both sides of the porous metal intermediate layer, and performing pore-forming treatment on the non-porous polymer layers to obtain the porous polymer layers.
[0028] Preferably, the first lithium-philic polymer is in-situ polymerized on a surface of the non-porous polymer layer that is away from the porous metal intermediate layer.
[0029] Preferably, after the first lithiophilic polymer is polymerized in situ, a second lithiophilic polymer is grafted onto the surface of the first lithiophilic polymer.
[0030] In a third aspect, the present invention further provides a battery, comprising the composite current collector as described in the first aspect or the composite current collector prepared by the preparation method as described in the second aspect.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] In the present invention, the porous polymer layer, the porous metal layer and the metal particles and the specific structure cooperate with each other; the porous polymer layer is located on both sides of the porous metal intermediate layer, so that the composite current collector has excellent mechanical flexibility, is not easy to break, can better avoid the short circuit of the battery, reduces the probability of thermal runaway, and greatly reduces the weight of the current collector. The density of the polymer is much lower than the density of the metal foil, thereby significantly improving the mass energy density of the battery core; the metal particles are synergistically filled in the porous polymer layer, which is in contact with the porous metal intermediate layer, which can improve the problem of poor conductivity caused by the presence of the polymer layer, and also plays a role in balancing the current density and promoting the rapid transmission of electrons. At the same time, the metal particles and the porous metal intermediate layer realize the connection of the conductive network on the front and back sides of the composite current collector, so there is no need to perform the pole ear welding at the pole ear position, avoiding the occurrence of the welding problem of the current collector; and the composite current collector structure provided by the present invention also promotes the Li + uniform deposition. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the SEM image of the current collector PAM@PDA@PPI-Cu-PPI provided in Example 1.
[0034] Figure 2 This is the SEM image of the composite current collector Cu / PAM@PDA@PPI-Cu-PPI provided in Example 1. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0037] In the description of this application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0038] In a specific embodiment, the present invention provides a composite current collector, the composite current collector comprising:
[0039] A porous metal intermediate layer;
[0040] A porous polymer layer, wherein the porous polymer layer is respectively located on two side surfaces of the porous metal intermediate layer;
[0041] The pores of the porous polymer layer are filled with metal particles.
[0042] In the present invention, the porous polymer layer, the porous metal layer and the metal particles and the specific structure cooperate with each other; the porous polymer layer is located on both sides of the porous metal intermediate layer, so that the composite current collector has excellent mechanical flexibility and is not prone to breakage. At the same time, it also improves the problem of poor conductivity caused by the presence of the polymer layer, reduces the probability of thermal runaway, and greatly reduces the weight of the current collector. The density of the polymer is much lower than the density of the metal foil, thereby significantly improving the mass energy density of the battery core; the metal particles are synergistically filled in the porous polymer layer, which is in contact with the porous metal intermediate layer, which can improve the problem of poor conductivity caused by the presence of the polymer layer, and also plays a role in balancing the current density and promoting the rapid transmission of electrons. At the same time, the metal particles and the porous metal intermediate layer realize the connection of the conductive networks on the front and back sides of the composite current collector, so there is no need to perform pole ear welding at the pole ear position, avoiding the occurrence of welding problems of the current collector; and the composite current collector structure provided by the present invention also promotes the Li + uniform deposition.
[0043] In the present invention, the synergistic cooperation of the porous polymer layer, the porous metal layer and the metal particles as well as the specific structure are indispensable. Without any one of the conditions, the purpose of promoting lithium ion deposition and inhibiting thermal runaway while improving energy density cannot be achieved.
[0044] As a preferred technical solution in a specific embodiment of the present invention, the metal material of the porous metal intermediate layer includes any one of copper, gold or silver, or a combination of at least two of them.
[0045] In the present invention, the metal elements in the porous metal intermediate layer are preferably consistent with the metal elements in the metal particles, and the electrical conductivity and thermal conductivity are better; the preferred metal element is copper, that is, the combination of the copper-based porous metal intermediate layer and the copper metal particles is more conducive to the improvement of electronic conductivity.
[0046] As a preferred technical solution in a specific embodiment of the present invention, the weight average molecular weight of the polymer in the porous polymer layer is 10,000~30,000, for example, 10,000, 13,000, 15,000, 18,000, 20,000, 23,000, 25,000, 28,000 or 30,000, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In the composite current collector provided by the present invention, the weight average molecular weight of the polymer in the porous polymer layer is 10,000-30,000, which is more conducive to improving the flexibility of the current collector.
[0048] As a preferred technical solution in a specific embodiment of the present invention, the polymer in the porous polymer layer includes any one of polyimide, polyvinylidene fluoride, polypropylene, polyethylene, polyethylene terephthalate, polymethyl methacrylate, polyethylene oxide or polyvinyl alcohol, or a combination of at least two thereof.
[0049] It should be noted that, in addition to the above-defined polymer material types, other conventional polymer material types that can be used for composite current collectors are also applicable to the present invention.
[0050] As a preferred technical solution in a specific embodiment of the present invention, the pore size in the porous polymer layer is 5~20μm, for example, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm or 20μm, etc.
[0051] As a preferred technical solution in a specific embodiment of the present invention, with the horizontal direction perpendicular to the thickness direction of the porous polymer layer, the center distance between the holes in adjacent porous polymer layers in the same horizontal direction is 500~5000μm, for example, 500μm, 1000μm, 1500μm, 2000μm, 2500μm, 3000μm, 3500μm, 4000μm, 4500μm or 5000μm, etc.
[0052] In the present invention, by further adjusting the pore size in the porous polymer layer to 5-20 μm and / or the hole center distance between adjacent holes in the porous polymer layer in the same horizontal direction to 500-5000 μm, the metal accumulation amount required for current collector welding can be better adapted to provide interlayer welding function.
[0053] As a preferred technical solution in a specific embodiment of the present invention, the thickness T1 of the porous polymer layer and the thickness T2 of the porous metal layer satisfy: 2μm≤T1+T2≤12μm, for example, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm or 12μm, etc.
[0054] Specifically, the thickness T1 of the porous polymer layer can be 1μm~10μm (for example, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm or 10μm, etc.); the thickness T2 of the porous metal layer can be 1μm~2μm (for example, 1μm, 1.5μm or 2μm, etc.); further regulating 2μm≤T1+T2≤12μm can not only obtain a battery cell structure with a higher energy density, but also better improve the structural stability to promote long cycle performance.
[0055] As a preferred technical solution in a specific embodiment of the present invention, the thickness T1 of the porous polymer layer and the thickness T2 of the porous metal layer satisfy: 1 / 2≤T1 / (T1+T2)≤10 / 12, for example 1 / 2, 7 / 12, 8 / 12, 9 / 12 or 10 / 12, etc.
[0056] The present invention regulates the thickness T1 of the porous polymer layer and the thickness T2 of the porous metal layer to satisfy: 1 / 2≤T1 / (T1+T2)≤10 / 12, which is more conducive to uniform deposition of lithium ions and can better exert the synergistic effect of the porous polymer layer and the porous metal layer.
[0057] As a preferred technical solution in a specific embodiment of the present invention, the porous polymer layer and the porous metal layer are further connected via the metal particles in the holes of the porous polymer layer.
[0058] In the present invention, the metal particles filled in the porous polymer layer are further connected with the porous metal layer, which enhances the electronic conductivity and is more conducive to the welding of the current collector.
[0059] As a preferred technical solution in a specific embodiment of the present invention, the surface of the porous polymer layer away from the porous metal layer is modified with a first lithium-philic polymer; the first lithium-philic polymer includes any one of polydopamine, polyethylene oxide, polyvinyl alcohol or polyacrylamide, or a combination of at least two of them.
[0060] In the present invention, the surface of the porous polymer layer is modified with a first lithium-philic polymer, which is beneficial for guiding Li + Attracts Li during charging on the positive electrode side + and the first lithium-philic polymer interacts with the porous polymer through hydrogen bonds and van der Waals forces, thereby achieving tight fixation of the first lithium-philic substance and the porous polymer layer.
[0061] As a preferred technical solution in a specific embodiment of the present invention, the surface of the porous polymer layer away from the porous metal layer is also modified with a second lithium-philic polymer, and the second lithium-philic polymer is grafted and connected to the first lithium-philic polymer; the second lithium-philic polymer includes any one of polydopamine, polyethylene oxide, polyvinyl alcohol or polyacrylamide, or a combination of at least two of them.
[0062] Polymer grafting is the process of connecting polymer chains through physical forces such as hydrogen bonds and polar bonds on polymer chain segments. This cross-linking does not require the participation of chemical reagents and is mainly achieved through the interaction between polymer molecular chains. The cross-linked structure is formed by mutual friction or pressure during the processing of the polymers.
[0063] In the present invention, the first lithiophilic polymer and the second lithiophilic polymer are different types of substances, and the second lithiophilic polymer is grafted and connected by the first lithiophilic polymer, so that both the first and second lithiophilic polymers have good lithium ion affinity, which can induce uniform nucleation of lithium metal and inhibit the growth of lithium dendrites.
[0064] In addition, the first lithiophilic substance has photosensitivity and can generate surface-bound free radicals to trigger surface-initiated free radical polymerization of various vinyl monomers, while the second lithiophilic polymer has a nanobrush structure. After the two are grafted, they can simultaneously exert the dual advantages of functional group characteristics and nanobrush structure, which is more conducive to the uniform deposition of lithium ions.
[0065] It should also be noted that the pore size in the porous metal intermediate layer of the present invention can be 5μm~20μm (for example, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, 17μm, 18μm or 20μm, etc.), and the center distance of the holes can be 500μm~5000μm (for example, 500μm, 1000μm, 1500μm, 2000μm, 2500μm, 3000μm, 3500μm, 4000μm, 4500μm or 5000μm, etc.), and those skilled in the art can make adaptive selections and adjustments based on actual needs.
[0066] In another specific embodiment, the present invention provides a method for preparing the composite current collector as described in the above specific embodiment, the preparation method comprising the following steps:
[0067] A porous polymer layer is composited on both sides of the porous metal intermediate layer, and then metal particles are filled in the holes of the porous polymer layer to obtain the composite current collector.
[0068] The preparation method provided by the present invention is simple and easy to operate, and can obtain a composite current collector structure with excellent performance, which is suitable for actual production and life.
[0069] As a preferred technical solution in another specific embodiment of the present invention, the method of composite porous polymer layers on both side surfaces of a porous metal intermediate layer includes: setting non-porous polymer layers on both side surfaces of the porous metal intermediate layer, performing pore-forming treatment on the non-porous polymer layer to obtain the porous polymer layer.
[0070] The method for forming pores in a polymer layer without pores in the present invention is a conventional technical solution, which can be used for forming pores in polymers without affecting their structure and performance, and the present invention is applicable to all such methods.
[0071] Exemplarily, the present invention provides a method for pore formation:
[0072] An ultraviolet picosecond laser drilling machine (LASER06007) is used to prepare the target holes in the polymer layer without holes.
[0073] As a preferred technical solution in another specific embodiment of the present invention, the first lithium-philic polymer is in-situ polymerized on the surface of the non-porous polymer layer away from the porous metal intermediate layer.
[0074] In the present invention, the method of in-situ polymerization of the first lithiophilic polymer can be adaptively selected and adjusted according to the specific material type of the first lithiophilic polymer.
[0075] Specifically, the present invention provides a method for in-situ polymerization of a first lithium-philic polymer:
[0076] The first lithium-philic polymer monomer undergoes a self-polymerization reaction on the surface of the polymer layer without pores to obtain the first lithium-philic polymer.
[0077] Optionally, the self-polymerization reaction is carried out in a solution, and the solution concentration of the first lithium-philic polymer monomer is 0.01 mol / L to 2 mol / L.
[0078] Optionally, the self-polymerization reaction is carried out under the condition of ultraviolet irradiation assistance, and the temperature of the self-polymerization reaction is 20°C~30°C.
[0079] As a preferred technical solution in another specific embodiment of the present invention, after the first lithiophilic polymer is in-situ polymerized, a second lithiophilic polymer is grafted onto the surface of the first lithiophilic polymer.
[0080] The present invention does not specifically limit the specific method of grafting the second lithium-philic polymer onto the surface, and the present invention is applicable to any method that can achieve polymer grafting.
[0081] Specifically, the present invention provides a surface grafting method, which comprises the following steps:
[0082] The second lithium-philic polymer monomer is polymerized on the surface of the first lithium-philic polymer to achieve grafting of the two.
[0083] Optionally, the polymerization reaction is carried out in a solution, and the solution concentration of the second lithium-philic polymer monomer is 0.01 mol / L to 2 mol / L, for example, 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L or 2 mol / L.
[0084] Optionally, the conditions of the polymerization reaction include: radiation polymerization under illumination conditions, the light source during the illumination process includes a 300W xenon lamp; the temperature of the polymerization reaction is 20°C~30°C, such as 20°C, 25°C or 30°C.
[0085] It should also be noted that:
[0086] The present invention does not specifically limit the method of composite porous polymer layers on both sides of the porous metal intermediate layer. The present invention is applicable to any method that can achieve interlayer composite of the porous metal intermediate layer and the porous polymer layer; and the order of composite is not limited.
[0087] Exemplarily, the present invention provides a specific method of compounding, the method comprising the following steps:
[0088] The non-porous polymer layer, the porous metal intermediate layer and the non-porous polymer layer are sequentially stacked and heat-treated to obtain a structure without pore-forming treatment;
[0089] The structure that has not been subjected to pore-forming treatment is subjected to pore-forming treatment of the polymer layer, so that the surfaces of both sides of the porous metal intermediate layer are composited with porous polymer layers.
[0090] The heat treatment temperature is 100°C to 500°C (e.g., 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C or 500°C, etc.), in order to ensure good and close contact between the polymer layer and the porous metal intermediate layer.
[0091] In addition, the present invention does not impose any special limitation on the filling method of the metal particles, and the present invention is applicable to any method for preparing the metal particles, such as the impregnation reduction method, the ethylene glycol reduction method, etc.
[0092] Specifically, the present invention provides a method for filling metal particles, the method comprising the following steps:
[0093] The composite structure, metal salt solution, precipitant solution and complexing agent solution are mixed and reacted to obtain metal hydroxide, which is then dehydrated to obtain metal oxide, and then subjected to reduction heat treatment to achieve the filling of metal particles in the pores of the porous polymer layer.
[0094] Further:
[0095] The mass ratio of the composite structure to the metal salt in the metal salt solution is (1 / 3-3):1, for example, 1 / 3:1, 0.5:1, 0.8:1, 1:1, 1.5:1, 2:1, 2.5:1 or 3:1, etc.
[0096] The precipitant solution includes an alkaline solution, and the alkaline solution includes a sodium hydroxide solution and / or a potassium hydroxide solution; the concentration of the precipitant solution is 0.01mol / L~3mol / L, for example, 0.01mol / L, 0.05mol / L, 0.1mol / L, 0.5mol / L, 1mol / L, 1.5mol / L, 2mol / L, 2.5mol / L or 3mol / L, etc.
[0097] The complexing agent solution includes (NH4)2S2O8 solution, and the mass fraction of the complexing agent solution is 5wt%~50wt%, for example, 5wt%, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt% or 50wt%, etc.
[0098] The reaction temperature is 30°C to 90°C, for example, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C or 90°C, and the reaction time is 3h to 36h, for example, 3h, 5h, 10h, 15h, 20h, 25h, 30h, 35h or 36h, etc.
[0099] The dehydration treatment method includes heat treatment, and the heat treatment temperature is 50°C to 150°C, for example, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C or 150°C.
[0100] The reduction heat treatment method includes performing reduction heat treatment under a reducing atmosphere, wherein the reducing atmosphere includes a hydrogen atmosphere or a mixed atmosphere containing a hydrogen atmosphere; the temperature of the reduction heat treatment is 100°C to 200°C, for example, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C or 200°C, etc.
[0101] In one embodiment, the present invention further provides a battery, comprising the composite current collector as described in one of the above embodiments or the composite current collector prepared by the preparation method described in another of the above embodiments.
[0102] The composite current collector provided by the present invention can be used in various types of battery structures, such as lithium ion batteries or sodium ion batteries, and is preferably used in lithium ion batteries.
[0103] Furthermore, the present invention does not impose any particular limitation on the specific type of lithium-ion batteries. For example, the present invention can be used in primary lithium-ion batteries (such as lithium metal batteries) or secondary lithium-ion batteries.
[0104] Furthermore, the composite current collector structure provided by the present invention is used in the electrode structure of a lithium-ion battery, can be used in a positive electrode sheet, and can also be used in a negative electrode sheet, and the composite current collector structure in the present application can be used for the preparation of a negative electrode-free battery, that is, the negative electrode is only a current collector structure; technical personnel in this field can make adaptive selections and adjustments based on actual needs.
[0105] Except for the composite current collector defined in the present invention, the present invention does not specifically limit the specific structure, preparation materials and preparation process of the battery, which are all conventional technical solutions.
[0106] Example 1
[0107] This embodiment provides a composite current collector, the composite current collector comprising:
[0108] A porous metal intermediate layer, i.e., a porous copper layer; a porous polymer layer, i.e., a porous polyimide layer, wherein the porous polymer layers are respectively located on both sides of the porous metal intermediate layer; and the pores of the porous polymer layer are filled with copper metal particles;
[0109] The pore size of the porous polymer layer is 5 μm, with the horizontal direction perpendicular to the thickness direction of the porous polymer layer as the horizontal direction, the hole center distance between adjacent holes in the porous polymer layer in the same horizontal direction is 500 μm, and the thickness T1 of the porous polymer layer is 1 μm;
[0110] The thickness T2 of the porous metal intermediate layer is 1 μm;
[0111] The surface of the porous polymer layer away from the porous metal layer is modified with a first lithium-philic polymer polydopamine (PDA) and a second lithium-philic polymer polyacrylamide (PMA); the first lithium-philic polymer is connected to the surface of the porous polymer layer through hydrogen bonds and van der Waals forces; and the first lithium-philic polymer polydopamine is grafted to the second lithium-philic polymer polyacrylamide.
[0112] The preparation method of the composite current collector is as follows:
[0113] (1) Preparation of a non-porous polymer layer polyimide film
[0114] 10mmol 4,4-diaminodiphenyl ether (ODA) and 10mmol pyromellitic anhydride (PMDA) were successively dissolved in 40mL N,N-dimethylacetamide (DMAc) solvent, and stirred at room temperature for 3-4 hours under nitrogen (N2) protection to obtain a polyamic acid (PAA) solution; then a catalyst mixture prepared by mixing pyridine and propionic anhydride (pyridine is 3wt% of PAA, and the molar ratio of propionic anhydride to PAA is 3:1) was quickly poured into the PAA solution, stirred at room temperature for 5 minutes, and then spin-coated; then placed in an oven, placed at 90°C for 30 minutes to obtain a PAA film after the solvent evaporated, and then heat treated at 200°C for 10 minutes, cooled to room temperature, and a 1μm thick polyimide film was obtained;
[0115] (2) Composite of porous polymer membrane layer and porous metal intermediate layer
[0116] A copper mesh (200 mesh, 2 μm diameter copper wire) was used as a porous metal intermediate layer, and the polyimide film, copper mesh, and polyimide film were stacked together in sequence, and treated at 100 ° C for 2 h to allow the layered structure to have good contact, and a PI-Cu-PI current collector was obtained;
[0117] 0.001 mol / L tris(hydroxymethyl)aminomethane hydrochloride (Tris-HCl) was prepared into a buffer solution with a pH of 8.5, and PI-Cu-PI was repeatedly washed with deionized water to remove impurities on its surface; the clean PI-Cu-PI foil was fixed to the bottom of an open container, and an appropriate amount of buffer solution was poured into the container; then 2 g / L dopamine was added to the solution, and the dopamine solution was irradiated with a 36-watt ultraviolet lamp. Due to the self-polymerization reaction of dopamine assisted by ultraviolet rays, the color of the solution turned into dark brown, and the current collector was taken out and dried at 80°C to obtain a PI-Cu-PI current collector modified with PDA;
[0118] The PI-Cu-PI current collector modified with PDA was immersed in a quartz bottle containing an aqueous solution of acrylamide monomer, the mass fraction of acrylamide monomer was 35%, and degassed by continuous dry nitrogen for 30 minutes at room temperature, and the quartz bottle was sealed; irradiated with a light source below 10 cm (300W xenon lamp simulating sunlight) for 1 hour, and the temperature was maintained at about 25°C. The copper foil after the polymerization reaction was cleaned with ethanol and dried under nitrogen to obtain a PDA@PAM / PI-Cu-PI composite current collector in which PDA was grafted with PMA;
[0119] A UV picosecond laser drilling machine (LASER06007) was used to prepare a hole structure with a pore size of 5 μm and a spacing of 0.5×0.5 mm in the polymer layer of the PDA@PAM / PI-Cu-PI composite current collector. The laser wavelength used was 355 nm and the spot focus diameter was 10 μm. The current collector structure PAM@PDA@PPI-Cu-PPI with composite porous polymer layers on both sides of the porous metal intermediate layer was obtained (the specific SEM image is shown in the figure). Figure 1 shown);
[0120] (3) Filling of copper metal particles into the pores of the porous polymer layer
[0121] PAM@PDA@PPI-Cu-PPI was placed in a mixed solution of 9 mL of 5 mol / L NaOH solution, 2 mL of 5 mol / L CuSO4 solution (the mass ratio of PAM@PDA@PPI-Cu-PPI to CuSO4 was 1:1), 11 mL of deionized water and 0.456 g of (NH4)2S2O8 and allowed to stand for 20 minutes. After being taken out, it was washed three times with anhydrous ethanol and deionized water respectively, and dried at 60°C for 12 hours to obtain a composite current collector with Cu(OH)2 grown between the pores of the porous polymer layer. The prepared Cu(OH)2 / PAM@PDA@PPI-Cu-PPI was then treated in an O2 atmosphere at 100°C for 2h to remove H2O from Cu(OH)2 to obtain CuO. Finally, the CuO in the pores was reduced to Cu elemental substance at a reduction heat treatment temperature of 120°C in a hydrogen atmosphere to obtain the composite current collector Cu / PAM@PDA@PPI-Cu-PPI (specific SEM images are shown in FIG. Figure 2 as shown).
[0122] Example 2
[0123] This embodiment provides a composite current collector, the composite current collector comprising:
[0124] A porous metal intermediate layer, i.e., a porous copper layer; a porous polymer layer, i.e., a porous polyimide layer, wherein the porous polymer layers are respectively located on both sides of the porous metal intermediate layer; and the pores of the porous polymer layer are filled with copper metal particles;
[0125] The pore size of the porous polymer layer is 10 μm, and the center distance between holes in adjacent porous polymer layers in the same horizontal direction perpendicular to the thickness direction of the porous polymer layer is 1000 μm, and the thickness T1 of the porous polymer layer is 10 μm;
[0126] The thickness T2 of the porous metal intermediate layer is 2 μm;
[0127] The surface of the porous polymer layer away from the porous metal layer is modified with a first lithium-philic polymer polydopamine (PDA) and a second lithium-philic polymer polyacrylamide (PMA); the first lithium-philic polymer is connected to the surface of the porous polymer layer through hydrogen bonds and van der Waals forces; and the first lithium-philic polymer polydopamine is grafted to the second lithium-philic polymer polyacrylamide.
[0128] The difference between the preparation method of this embodiment and that of embodiment 1 is as follows:
[0129] In step (1), the spin coating thickness is adjusted to obtain a polyimide film with a thickness of 10 μm;
[0130] In step (2), the thickness of the copper mesh and the pore-making parameters of the UV picosecond laser drilling machine are adjusted, and the preparation parameters of the first lithium-philic polymer are adjusted as follows: 1 g / L dopamine is added, 6 mL of 5 mol / L NaOH solution, 1 mL of 5 mol / LCuSO4 solution (the mass ratio of PAM@PDA@PPI-Cu-PPI to CuSO4 is 3:1), 5 mL of deionized water and 0.3 g of a mixed solution of (NH4)2S2O8.
[0131] The rest of the preparation methods and parameters were the same as those in Example 1.
[0132] Example 3
[0133] This embodiment provides a composite current collector, the composite current collector comprising:
[0134] A porous metal intermediate layer, i.e., a porous copper layer; a porous polymer layer, i.e., a porous polyimide layer, wherein the porous polymer layers are respectively located on both sides of the porous metal intermediate layer; and the pores of the porous polymer layer are filled with copper metal particles;
[0135] The pore size of the porous polymer layer is 20 μm, with the horizontal direction perpendicular to the thickness direction of the porous polymer layer as the horizontal direction, the center distance between the holes in the adjacent porous polymer layers in the same horizontal direction is 5000 μm, and the thickness T1 of the porous polymer layer is 2 μm;
[0136] The thickness T2 of the porous metal intermediate layer is 1.5 μm;
[0137] The surface of the porous polymer layer away from the porous metal layer is modified with a first lithium-philic polymer polydopamine (PDA) and a second lithium-philic polymer polyacrylamide (PMA); the first lithium-philic polymer is connected to the surface of the porous polymer layer through hydrogen bonds and van der Waals forces; and the first lithium-philic polymer polydopamine is grafted to the second lithium-philic polymer polyacrylamide.
[0138] The difference between the preparation method of this embodiment and that of embodiment 1 is as follows:
[0139] In step (1), the spin coating thickness is adjusted to obtain a 2 μm thick polyimide film;
[0140] In step (2), the thickness of the copper mesh and the diameter of the copper wire (1 μm) and the hole-making parameters of the UV picosecond laser drilling machine are adjusted.
[0141] The rest of the preparation methods and parameters were the same as those in Example 1.
[0142] Example 4
[0143] The difference between this embodiment and embodiment 1 is that the polymer in the porous polymer layer in this embodiment is polypropylene, the first lithiophilic polymer is polyethylene oxide, and the second lithiophilic polymer is polyvinyl alcohol.
[0144] In the preparation method: a polypropylene film is directly selected and compounded with a porous intermediate layer;
[0145] The first lithiophilic polymer monomer is ethylene oxide, and the second lithiophilic polymer monomer is vinyl alcohol;
[0146] The rest of the preparation methods and parameters were the same as those in Example 1.
[0147] Example 5
[0148] The difference between this embodiment and embodiment 1 is that the composite current collector provided in this embodiment does not contain the second lithium-philic polymer polyacrylamide (PMA).
[0149] In the preparation method, the preparation process of PMA is not carried out.
[0150] The rest of the preparation methods and parameters were the same as those in Example 1.
[0151] Example 6
[0152] The difference between this embodiment and embodiment 1 is that the composite current collector provided in this embodiment does not contain the first lithium-philic polymer and the second lithium-philic polymer.
[0153] In the preparation method, after the PI-Cu-PI current collector is obtained, copper metal particles are directly filled.
[0154] The rest of the preparation methods and parameters were the same as those in Example 1.
[0155] Example 7
[0156] The difference between this embodiment and embodiment 1 is that in the composite current collector provided in this embodiment, the porous metal intermediate layer is a silver layer, and the metal particles are silver particles.
[0157] In the preparation method, in step (2), a silver wire mesh (silver wire mesh 200 mesh, the diameter of the holes in the silver wire is 2 μm) is used as the porous metal intermediate layer;
[0158] The metal salt solution in step (3) is a silver nitrate solution.
[0159] The rest of the preparation methods and parameters were the same as those in Example 1.
[0160] Example 8
[0161] The difference between this embodiment and embodiment 1 is that the pore size of the porous polymer layer in this embodiment is 1 μm.
[0162] In the preparation method, the hole-making parameters of the ultraviolet picosecond laser drilling machine are adjusted.
[0163] The rest of the preparation methods and parameters were the same as those in Example 1.
[0164] Example 9
[0165] The difference between this embodiment and embodiment 1 is that the pore size of the porous polymer layer in this embodiment is 25 μm.
[0166] In the preparation method, the hole-making parameters of the ultraviolet picosecond laser drilling machine are adjusted.
[0167] The rest of the preparation methods and parameters were the same as those in Example 1.
[0168] Example 10
[0169] The difference between this embodiment and embodiment 1 is that in the composite current collector provided in this embodiment, the thickness T2 of the porous metal intermediate layer is 5 μm, that is, T1 / (T1+T2)=1 / 6.
[0170] The rest of the preparation methods and parameters were the same as those in Example 1.
[0171] Embodiment 11
[0172] The difference between this embodiment and embodiment 1 is that in step (2) of this embodiment, the PI-Cu-PI current collector is directly modified with a polydopamine material. The specific method is: directly compounding polydopamine with the PI-Cu-PI current collector. The compounding process is: directly coating a polydopamine aqueous solution with a concentration of 2 mol / L on the surface of the PI-Cu-PI current collector, and drying to obtain a PI-Cu-PI current collector modified with a polydopamine material.
[0173] The rest of the preparation methods and parameters were the same as those in Example 1.
[0174] Comparative Example 1
[0175] The difference between this comparative example and Example 1 is that in this comparative example, only the copper mesh in Example 1 is used as the current collector;
[0176] The current collector structure provided in this comparative example cannot be welded, and it is difficult to prepare a complete battery structure.
[0177] Comparative Example 2
[0178] The difference between this comparative example and Example 1 is that in this comparative example, the porous metal intermediate layer is replaced by a copper foil without holes.
[0179] The rest of the preparation methods and parameters were the same as those in Example 1.
[0180] Comparative Example 3
[0181] The difference between this comparative example and Example 1 is that the current collector in this comparative example is a copper foil current collector, and the parameter is that the thickness is 8 μm.
[0182] Comparative Example 4
[0183] The difference between this comparative example and Example 1 is that copper metal particles are not filled in the composite current collector provided in this comparative example.
[0184] In the preparation method, step (3) is not performed.
[0185] The rest of the preparation methods and parameters were the same as those in Example 1.
[0186] The current collectors provided in Examples 1-11 and Comparative Examples 1-4 were applied to battery structures and performance tests were performed.
[0187] ) Preparation of negative electrode-free battery
[0188] The prepared composite current collector is used as a negative electrode-free current collector, that is, a negative electrode sheet, and the current collector size is (100 mm × 55 mm);
[0189] Preparation of positive electrode sheet: NCM811 is used as the positive electrode active material, carbon black is used as the conductive agent, and PVDF is used as the binder. The positive electrode active material, the conductive agent, and the binder are mixed in a mass ratio of 97:1:2, and N-methylpyrrolidone (NMP) is added to prepare the positive electrode slurry. The solid content is controlled to be 65%~70%. 12μm aluminum foil is used as the positive electrode current collector. The positive electrode sheet is prepared by coating and drying. The size of the positive electrode sheet is 96mm×51mm.
[0190] Celgard2320 microporous polypropylene film was used as a separator; the electrolyte was 1 mol / L LiPF6 dissolved in a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a 1:1 volume ratio;
[0191] The capacity ratio of the positive electrode to the negative electrode is 1. The assembly process adopts a soft-pack lamination method. Lamination: the positive electrode sheet, the separator, and the negative electrode current collector are stacked in order to obtain a battery cell; then assembly is performed: the stacked battery cell is hot-pressed and placed in an aluminum-plastic film, and the top and side are sealed. The electrolyte is injected into the battery, and the battery after injection is sealed. The injection coefficient is 3g / Ah. The packaged battery is subjected to a formation treatment to obtain a battery to be tested.
[0192] ) Battery performance test
[0193] (a) Energy density: First, weigh each group of tested batteries and record the mass of the battery as m. Then, at 25°C, charge the battery at a constant current of 0.1C to 4.25V, then charge it at a constant voltage of 4.25V to a current ≤0.05C. After standing for 5 minutes, discharge it at a constant current of 0.1C to 2.8V to obtain the discharge energy Q. The battery energy density is calculated as Q / m.
[0194] (b) Cycle performance: 1. Take the battery after capacity division and first charge it to 4.25V with a constant current of 1C, and then charge it to I≤0.05C with a constant voltage of 4.25V; 2. After standing for 5 minutes, discharge the battery to 2.8V with a constant current of 1C to obtain the discharge capacity C1; 3. Stand for 30 minutes. Repeat steps 1-3 1999 times to obtain the discharge capacity C2000; the capacity retention rate after 2000 cycles is calculated as (C2000) / (C1)*100%.
[0195] (c) Thermal runaway peak temperature test method: in accordance with T / CSAE 344-2024 "Adiabatic thermal test method for thermal runaway of lithium-ion power batteries".
[0196] The test results of the above tests are shown in Table 1.
[0197] Table 1
[0198]
[0199] In summary, in the present invention, the porous polymer layer, the porous metal layer and the metal particles and the specific structure cooperate with each other; the porous polymer layer is located on both sides of the porous metal intermediate layer, so that the composite current collector has excellent mechanical flexibility, is not easy to break, can better avoid the short circuit of the battery, reduces the probability of thermal runaway, and greatly reduces the weight of the current collector. The density of the polymer is much lower than the density of the metal foil, thereby significantly improving the mass energy density of the battery core; the metal particles are synergistically filled in the porous polymer layer, which is in contact with the porous metal intermediate layer, which can improve the problem of poor conductivity caused by the presence of the polymer layer, and also plays a role in balancing the current density and promoting the rapid transmission of electrons. At the same time, the metal particles and the porous metal intermediate layer realize the connection of the conductive network on the front and back sides of the composite current collector, so there is no need to perform pole ear welding at the pole ear position, avoiding the occurrence of welding problems of the current collector; and the composite current collector structure provided by the present invention also promotes the Li + uniform deposition.
[0200] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A composite current collector, characterized in that: The composite current collector comprises: A porous metal intermediate layer; A porous polymer layer, wherein the porous polymer layer is respectively located on two side surfaces of the porous metal intermediate layer; The pores of the porous polymer layer are filled with metal particles; the porous polymer layer and the porous metal intermediate layer are also connected through the metal particles in the pores of the porous polymer layer; the surface of the porous polymer layer away from the porous metal intermediate layer is modified with a first lithium-philic polymer; the surface of the porous polymer layer away from the porous metal intermediate layer is also modified with a second lithium-philic polymer, and the second lithium-philic polymer is grafted and connected to the first lithium-philic polymer; The first lithium-philic polymer has a photosensitive property; the second lithium-philic polymer has a nanobrush structure; The preparation method of the composite current collector comprises the following steps: A porous polymer layer is composited on both sides of the porous metal intermediate layer, and then metal particles are filled in the holes of the porous polymer layer to obtain the composite current collector.
2. The composite current collector according to claim 1, characterized in that: The metal material of the porous metal intermediate layer includes any one of copper, gold or silver, or a combination of at least two of them.
3. The composite current collector according to claim 1, characterized in that: The porous polymer layer satisfies at least one of the following conditions (a) to (d): (a) the weight average molecular weight of the polymer in the porous polymer layer is 10,000 to 30,000; (b) the polymer in the porous polymer layer includes any one or a combination of at least two of polyimide, polyvinylidene fluoride, polypropylene, polyethylene, polyethylene terephthalate, polymethyl methacrylate, polyethylene oxide or polyvinyl alcohol; (c) the pore size in the porous polymer layer is 5 to 20 μm; (d) With the thickness direction perpendicular to the porous polymer layer as the horizontal direction, the center distance between holes in adjacent porous polymer layers in the same horizontal direction is 500-5000 μm.
4. The composite current collector according to claim 1, characterized in that: The porous polymer layer and the porous metal intermediate layer satisfy at least one of the following conditions (e) to (g): (e) the thickness T1 of the porous polymer layer and the thickness T2 of the porous metal intermediate layer satisfy: 2 μm ≤ T1 + T2 ≤ 12 μm; (f) The thickness T1 of the porous polymer layer and the thickness T2 of the porous metal intermediate layer satisfy: 1 / 2≤T1 / (T1+T2)≤10 / 12.
5. The composite current collector according to claim 1, characterized in that: The first lithium-philic polymer includes any one of polydopamine, polyethylene oxide, polyvinyl alcohol or polyacrylamide, or a combination of at least two thereof.
6. The composite current collector according to claim 5, characterized in that: The second lithium-philic polymer includes any one of polydopamine, polyethylene oxide, polyvinyl alcohol or polyacrylamide, or a combination of at least two thereof.
7. A method for preparing a composite current collector according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: A porous polymer layer is composited on both sides of the porous metal intermediate layer, and then metal particles are filled in the holes of the porous polymer layer to obtain the composite current collector.
8. The preparation method according to claim 7, characterized in that: The method for composite porous polymer layers on both sides of the porous metal intermediate layer comprises: arranging non-porous polymer layers on both sides of the porous metal intermediate layer, and performing pore-forming treatment on the non-porous polymer layers to obtain the porous polymer layers.
9. The preparation method according to claim 8, characterized in that: The first lithium-philic polymer is in-situ polymerized on the surface of the non-porous polymer layer away from the porous metal intermediate layer.
10. The preparation method according to claim 9, characterized in that: After the first lithiophilic polymer is polymerized in situ, a second lithiophilic polymer is grafted onto the surface of the first lithiophilic polymer.
11. A battery, characterized in that: The battery comprises the composite current collector according to any one of claims 1 to 6 or the composite current collector prepared by the preparation method according to any one of claims 7 to 10.
Citation Information
Patent Citations
Ultrathin flexible electrode current collector
CN215869466U
Preparation method and application method of lithium battery negative electrode current collector surface modifier for preventing lithium dendrite deposition
CN111446452A
Current collector and preparation method thereof, negative electrode and electrochemical energy storage device
CN115440986A